Pengaruh Marketing Mix terhadap Peningkatan Produktifitas Hasil Tangkap Ikan Masyarakat Pesisir Kendal - Diah Kusumawati, Evyana; Karjono, Karjono; Karmanis, Karmanis (Majalah Ilmiah Gema Maritim, 2024)
The phenomenon currently faced by fishermen is not only about the large potential of fish in Kendal Regency but also the problem of marketing fishermen's catches. Due to the perishable nature of fishery products, marketing has a big influence on fishermen's income. The decline in the quality of marine products is a result of poor marketing distribution channels, so the selling price will fall and the income of fishermen in the Kendal community will decrease. Apart from that, if the fish is not fresh, the middlemen don't want to buy it so the fish doesn't sell. Therefore, it is necessary to carry out research regarding fish marketing to increase fishermen's income. The purpose of this research is to find out and analyze whether the marketing mix has a significant influence on increasing the productivity of fish catches in the Kendal coastal community and find out how much influence the marketing mix has on increasing the productivity of the fish catch in the Kendal coastal community). The type of method used in this research is quantitative, where the number of respondents or samples taken was 50 fishermen out of 100 fishermen. The data collection used was the questionnaire method. The results of the discussion, show that "There is an influence of the marketing mix (X) on increasing the productivity of fish catches (Y)". where the significance value (Sig.) is 0.004 (smaller than the probability value of 0.05), this means that H0 is rejected and H1 is accepted. Meanwhile, the magnitude of the influence of noodle marketing, both in terms of product, price, distribution and promotional methods, has an 82.7% increase in fish catch productivity, shown by an R Square of 0.827.